2006
DOI: 10.1300/j158v06n03_02
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Influence of Perceived Parenting Practices on Depression and Substance Use Among African American Juvenile Offenders

Abstract: The primary purpose of this study was to examine whether perceived parenting practices were related to and predictive of depression and substance use among 119 African American juvenile offenders. Findings revealed that maternal practices were related to and predictive of depression, with maternal roles accounting for most of the variance. Paternal practices were related to and predictive of substance use with paternal roles and affective involvement accounting for most of the variance. Taken together, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The concept of out from school to the prison pipeline is a worrying trend as more students gradually become disengaged from their school and simultaneously move towards involvement in crime and delinquency (Sander et al, 2012;Christle et al, 2005). This is especially worrying as these adolescents are likely to associate with delinquent peers, who are often themselves drug-using peers (Kung and Farrell, 2000;Caldwell et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of out from school to the prison pipeline is a worrying trend as more students gradually become disengaged from their school and simultaneously move towards involvement in crime and delinquency (Sander et al, 2012;Christle et al, 2005). This is especially worrying as these adolescents are likely to associate with delinquent peers, who are often themselves drug-using peers (Kung and Farrell, 2000;Caldwell et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Family situations are important factors that influence delinquent behaviour (Murry et al, 2006) and even substance use (Caldwell et al, 2006;Kung and Farrell, 2000). More juvenile offenders come from broken homes than intact family systems (Gregory, 1965;Hoffman and Brown, 1998;Demuth and Brown, 2004) as seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Brody, Chen, et al (2006) found similar buffering results with regard to the relation between discrimination and conduct problems. More generally, supportive parenting has been associated with less adolescent substance use in a number of studies (e.g., Caldwell et al, 2006). We examined this buffering process in both of the current studies, with the assumption that supportive parenting would buffer against hostile/angry reactions to discrimination, resulting in less willingness to use substances.…”
Section: What Moderates the Discrimination → Use Relation?mentioning
confidence: 99%
“…[18,25,27-29,31-33] At the familial level, a lack of communication, or cohesion, between family members and as well as parental substance use have been found to be associated with adolescent misuse of alcohol. [34-39] On the other hand, strong family bonds [40,41] and parental monitoring [28,33,35,42] have been found to protect against alcohol use and the progression into alcohol-related problems.…”
Section: Introductionmentioning
confidence: 99%